Pengaruh Infusa Jahe Merah (Zingiber officinale var. Rubrum) terhadap Pertumbuhan Bakteri Streptococcus mutans - Nugraha, Yogi Rahman; Rohdiana, Aulia; Nurul; Wardani, Diah (LP4M STIKes Karsa Husada Garut, 2024)
Oral infections remain a significant public health problem in Indonesia, with dental caries being highly prevalent and primarily associated with Streptococcus mutans. The use of modern antibiotics for caries treatment often leads to side effects and bacterial resistance, prompting the search for herbal-based alternatives. Red ginger (Zingiber officinale var. rubrum) contains bioactive compounds such as flavonoids, phenols, gingerol, shogaol, and essential oils, which are known for their antibacterial activity. This study aimed to evaluate the inhibitory effect of red ginger infusion on the growth of S. mutans. A Posttest Control Group design was employed, and antibacterial activity was assessed using the disk diffusion method. Treatments consisted of a negative control (distilled water), a positive control (ciprofloxacin 5 µg), and red ginger infusion (RGI) at concentrations of 10%, 20%, and 40%. Results demonstrated an increase in inhibition zone diameter with higher concentrations of RGI. The negative control produced no inhibition, while the positive control showed the largest inhibition zone (45.05 mm). RGI at 10% yielded 7.91 mm (p=0.408), 20% yielded 14.81 mm (p=0.066), and 40% yielded 23.05 mm (p=0.022). Only the 40% concentration showed a statistically significant difference compared to the negative control (p<0.05). These findings indicate that red ginger infusion possesses antibacterial activity against S. mutans, although its effectiveness is still below that of ciprofloxacin. Therefore, red ginger may be considered as a potential herbal alternative for dental caries prevention, particularly as a supportive therapy. Further studies are required to isolate active compounds and develop more effective topical formulations.